The problem with dyes in infection control. (November 2017) - Wainwright, Mark
Abstract: Photoantimicrobial - i.e. light-activated - antimicrobial agents constitute a subset of compounds from a variety of dye classes, mainly synthetic. However, in terms of clinical acceptance, this identification as 'dye' is disadvantageous. The following is an attempt, via rationalisation and precedent, to put the case for the medical use of photoantimicrobials, at a time of an accepted need for alternative approaches to infection control, beside that of conventional antimicrobial drugs. Note: the term antibiotic is employed here with the everyday, rather than the scientific, meaning, i.e. rather than antibacterial . Highlights: Photosensitising dyes and light can be effective antimicrobials. Photoantimicrobials are effective against all microbial types. Effective clinical work is increasingly reported. Efficacy against drug-resistant microbial pathogens is particularly important.